Lessing, Schlegel, and Romantic Enlightenment. On the incidence of Lessing in Schlegel’s critique - Miñambres, Germán Garrido (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Along with Goethe, Lessing is the modern author to whom Friedrich Schlegel devoted the most attention. The 1804 prologue On the Essence of Criticism is considered indispensable for understanding the notion of criticism he develops throughout his work. However, influential authors such as Manfred Frank have prioritized Jacobi and his concept of feeling (Gefühl) in the philosophical origins of early Romanticism. This paper argues that Lessing was a referent of critical thought in Schlegel’s early approaches to transcendental criticism. In particular, his early philosophical fragments presume a notion of critical thinking repeated in his 1797 review of Lessing and his characterization of Nathan.